A study on restaurant mcdonald’s Malaysia Bukit Bintang and their impact customer satisfaction in term of location, price and value, food safety, convenience and business hour - Idrus, Shah Rizal (2007)
The purpose of this research is to study on quality of fast food restaurant provided by Restaurant McDonald's Bukit Bintang Kuala Lumpur and their impact on customer satisfaction. This quality of services provided include the location of the restaurant, the prices and value, the attitude and personality of the employees and the types of services provided by Restaurant McDonald's Malaysia. The study tries to determine the relationship or the factor that influence the frequency of customer visit. The study was conducted at Restaurant McDonald's Malaysia Bukit Bintang, Kuala Lumpur. This branch covers wide areas with limited employees. Therefore, the researcher would like to determine the quality of services provided and their impact on customer satisfaction.